PENGARUH LEADERSHIP DAN COMMUNICATION TERHADAP PERFORMANCE EMPLOYEE PADA PT. ISS INDONESIA SUKOREJO PASURUAN - Bahtiar Prabowo (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2018)
The purpose of this study was to determine the significant effect of leadership andcommunication styles on employee performance. The population in this study was 140people, and samples were taken using purposive sampling with the criteria of group Cemployees as many as 35 people. The analytical analysis used is multiple linear regression.The results of this study shown that the coefficient of determination (R2) are 0.915, this meanthat 91.5% of the performance variables will be influenced by leadership style andcommunication while the remaining 8.5% performance variables are influenced by othervariable. The results of the F test show that leadership and communication stylessimultaneously have a significant effect on employee performance because F-test has greaterthat F-table 172.631 and the value of significance is 0.00. While the results of the t-test forleadership style variables are obtained by t-test greater than t-table that is 6.803 > 2, thismeans that leadership styles have a significant effect on employee performance, and forcommunication variables has value of t-test greater than t-table are 5.159> 2.037 socommunication has as partially has significant effect on employee performanceKeywords: Leadership style, Communication and Performance